A case report of secondary syphilis with clinical features that should not be missed - Gani, Abdul H. M.; Seyam, Naheel I. (International Journal of Research in Medical Sciences, 2023)
We present a clinical case of a 22-year-old man who had a sore throat for a month. Further examination and history revealed that he had secondary syphilis, which was confirmed by a positive laboratory test. This case emphasizes the importance of conducting a thorough history and physical examination to avoid missed diagnoses.